SOSIALISASI INOVASI RUMAH APUNG SEBAGAI STRATEGI TANGGAP BENCANA DI KECAMATAN PANJANG - Fadhilah Rusmiati; Ayu Komalasari Dewi; Tiya Suryadi Putri; Moh. Faisal Faris (Nemui Nyimah, 2026)
Panjang Subdistrict, located in Bandar Lampung City, is a coastal area vulnerable to tidal flooding and coastal abrasion due to climate change and rising sea levels. This Community Service Program (PKM) aims to enhance community knowledge and preparedness through the dissemination of floating house innovations as an environmentally based disaster response strategy. The methods employed in this program include coordination with local government authorities, field observations, problem identification, formulation of adaptive solutions, and socialization activities using visual educational media such as posters, leaflets, and information boards. The results indicate that the community still has limited understanding of coastal disaster mitigation. Therefore, the service team introduced three main innovations: floating houses as an adaptive architectural response to rising sea levels, biopore infiltration holes to improve soil absorption and reduce waterlogging, and retaining walls as protection against coastal abrasion. The socialization process was carried out through interactive discussions and simulations of simple innovation applications involving active community participation. The outcomes demonstrate an increase in community awareness, knowledge, and participation in disaster mitigation efforts, further supported by the installation of mitigation signage and evacuation maps in the coastal area. Overall, this program contributes to the development of a resilient, adaptive, and sustainable coastal community in facing disaster threats